Hemostasis using purse‐string reefing with endoscopic clip and endoloop for a huge hematoma after cold snare polypectomy. Issue 4 (18th March 2022) - Negishi, Ryoju; Muramoto, Takashi; Ohata, Ken
Abstract : Watch a video of this article.